Antenatal and postnatal risk factors of obesity in children age 2-5 years old in Yogyakarta District, Indonesia - Yudha Patria, I Ketut Rutin Pastadita Sunartini (Universitas Gadjah Mada, 2012)
Obesity and overweight have become a health issue throughout the world, with a dramaticincrease in prevalence each year. An obese child is thought to be adorable, but parents are notaware of the health risk it holds. Preventive measures by decreasing the risk factors for obesityare more effective than treating the problem. The aim of this study was to identify the riskfactors of obesity in antenatal and postnatal period in children in Yogyakarta District. This wasan observational study with a case control design. Criteria of obesity were defined according toWHO 2006 growth chart. Subjects were children age 2 to 5 years old that were enrolled inplaygroups in the Yogyakarta Distric with a targeted sample size of 41 children. Parents ofchildren that met the inclusion and exclusion criteria were given questionnaires to fill out. Theresults were analyzed using bivariate analysis and multivariate logistic regression. Thirty fourobese children and 34 non obese children (as control) were explored for the obesity risk factors.Prematurity/gestational age (OR=16; 95%CI=3.27-78.28; p=0.001), passive smoking (OR=5.50;95%CI=1.90-15.96; p=0.001), low birth weight (OR=7.27; 95%CI=1.45-36.47; p=0.008),eating more than 3 times daily (OR=2.19; 95%CI=1.66-2.89; p=0.007), meals that are high inlipid (OR=4.18; 95%CI=1.45-12.02; p=0.007) were shown to be risk factors for obesity inchildren. Factors such as picky eaters (OR=0.16; 95%CI=1.45-12.02; p=0.002), early introductionto solid food (OR=0.29; 95%CI=0.10-0.79; p=0.01), exercise (OR=0.25; 95%CI=0.06-0.32;p=0.04), and watching TV or playing video game under 2 hours daily (OR=0.30; 95%CI=0.09-0.95; p=0.04) were identified as protective factors against obesity. By using the multivariateanalysis, there were only 2 risk factors for obesity i.e. eating more than 3 times daily andprematurity/gestational age and there were only 2 protective factors i.e. exercise and introductionto solid food that remained statistically significant as independent factors influencing obesity inchildren aged 2 to 5 years old in the Yogyakarta District.Keywords: obesity - children age 2 to 5 years old - antenatal - postnatal - risk factors